Learning and Learning Conditions and Bloom Taxonomy and Islamic Education - La Ode Muhamad Risal; Amiruddin; Azlin; Saprin (al-Afkar, Journal For Islamic Studies, 2025)
This research discusses learning and learning conditions as well as Bloom's Taxonomy and Islamic Education. The type of research in this article is qualitative descriptive research. Apart from that, this research is of a library nature (library research). The results of this research show that supportive learning conditions, combined with Bloom's Taxonomy framework, enable a more effective and comprehensive Islamic education process. By paying attention to learning conditions in accordance with the needs of the cognitive, affective and psychomotor domains, Islamic education can form individuals who not only have good religious knowledge but also have noble morals and skills that are able to practice religious teachings in everyday life.